The Functional Assessment of Patients in the Period of Neurosurgical Treatment - Robert Ślusarz; Agnieszka Królikowska; Renata Jabłońska; Beata Haor; Anna Antczak; Karolina Filipska; Barbara Smarszcz; Maciej Śniegocki (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The interests of scientists, especially in the field of medicine and health science, contemplate the functional condition of patient in recent years. Proper functional capacity with good state of being and psychological attitude are the most important health indicators. Proper functional capacity is defined as the ability for independent performance and covering of basic vital needs, e.g. the control of the sphincter, nutrition, mobility and maintaining proper hygiene. The proper functional capacity of the whole system of vital activities means independence. Aim. The main aim of this study was the functional assessment of patients in the period of neurosurgical treatment. Material and Methods. The study included 415 patients hospitalized on neurosurgical wards. The functional capacity of patients was assessed twice (on the day of admission — Assessment 1 and on the day of discharge — Assessment 2). Functional capacity was analyzed using Functional Capacity Scale (FCS). The direct observation with measurement technique was used. The research proposal was approved by the bioethics committee. Results. On the day of admission, most of the patients (n=249; 60%), showed independence. Most of the independent patients were in the group of patients with tumors — 138 (83.6%), the second group were patients with brain aneurysm — 63 (63.0%) and the third group were patients with trauma — 48 (32.0%) (p<0.05). Most of the patients (n=314; 76%) were independent on the day of discharge. Among them, there were patients with brain tumor — 127 (77.0%), trauma — 112 (74.7%) and aneurysm — 75 (75.0%) (p>0.05). Conclusions. Most of the patients after neurosurgical treatment showed better functional capacity when compared with the period before it. Patients with brain tumors showed considerably better functional capacity on the day of admission when compared with patients with trauma or aneurysm. (JNNN 2016;5(2):46–52)